Efficient modelling of mid to high frequency underwater acoustic propagation - Duncan, Alexander; Parnum, Iain; Henley, Peter (Australian Acoustical Society, 2013)
Accurate prediction of the acoustic interference field at mid to high frequencies is computationally intensive, even for ray theory based models, and is of little practical use because the fine detail of the interference pattern is sensitive to the exact values of environmental parameters, such as bathymetry and sound speed, that are inherently uncertain. This paper considers an alternative approach in which a much faster incoherent beam model is used to compute the mean acoustic field, and the interference is treated as a statistical process based on a Rayleigh amplitude distribution. Excellent agreement was found between interference field statistics obtained using this hybrid approach, and those resulting from a full coherent transmission loss calculation whenever the horizontal separation between source and receiver was sufficiently large that there were many contributing ray paths.